Seroprevalence of Larval Toxocarosis in the Czech Republic - Skulinova, Katerina; Novak, Jan; Kasny, Martin; Kolarova, Libuse (Acta Parasitologica, 2020)
BACKGROUND: Larval toxocarosis (LT), a zoonotic disease transmitted by dogs, cats, and other carnivores, is caused by roundworms of the genus Toxocara. Humans become infected by ingesting embryonated eggs of this parasite. In this study, we present data on the seroprevalence of LT in the Czech Republic collected by the National Reference Laboratory for Tissue Helminthoses in 2012-2016. METHODS: Using enzyme-linked immunosorbent assay, a total of 4428 adults and children with or without clinical symptoms were examined for the presence of IgG antibodies against Toxocara canis excretory-secretory antigens. RESULTS: Of all the persons examined, specific Toxocara antibodies were detected in 160 (3.6%) individuals. There were, however, significant differences between various regions, with seropositivity rates ranging from 1.4 to 7.5%. CONCLUSION: In comparison to studies from 1998 and 2004, our results suggest a decrease in overall Toxocara seroprevalence in the Czech population, whereby the rates are similar to or even lower than rates in some other Central European countries.
Keywords: Female; lidé středního věku; Animals; novorozenec; Adolescent; Larva; mužské pohlaví; protilátky helmintové; toxokaróza; mladý dospělý; Immunoglobulin G; Zoonoses; Enzyme-Linked Immunosorbent Assay; kojenec; Humans; Infant; dospělí; zoonózy; Toxocariasis; Antibodies, Helminth; Child, Preschool; Toxocara; Czech Republic; lidé; Seroepidemiologic Studies; Middle Aged; zvířata; séroepidemiologické studie; senioři; ELISA; ženské pohlaví; imunoglobulin G; Child; Česká republika; Aged; předškolní dítě; Young Adult; dítě; Adult; Infant, Newborn; Male; mladiství; larva